Outcomes and Left Ventricular Ejection Fraction in Cardiac Magnetic Resonance: Challenging the “Higher Is Better” - Rungroj Krittayaphong; Thammarak Songsangjinda; Kanchalaporn Jirataiporn; Ahthit Yindeengam (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Contradictory evidence exists regarding the correlation between supranormal left ventricular ejection fraction (LVEF) and adverse outcomes. This study aimed to elucidate the prognostic value of supranormal LVEF. Methods This retrospective cohort study analyzed patients referred for cardiac magnetic resonance imaging to assess myocardial ischemia or viability. Subjects were stratified into eig8ht LVEF groups: <20%, 20% to 30%, 30% to 40%, 40% to 50%, 50% to 60%, 60% to 70%, 70% to 80%, and ≥80%. Primary outcomes included cardiovascular death, heart failure, myocardial infarction, and stroke. The extracellular volume fraction was measured. Results The study cohort comprised 3279 patients (mean age 68.0±12.7 years; 64.0% female). The group with 60% to 70% LVEF had the lowest risk and was used as the reference group. The median follow‐up was 41.4 months (interquartile range, 33.9–49.7 months). The group with LVEF <20% exhibited the highest composite outcome risk (unadjusted hazard ratio [HR], 6.77 [95% CI, 3.81–12.03]; P<0.001; adjusted HR, 2.68 [95% CI, 1.28–5.62]; P<0.001). The groups with LVEF 70% to 80% and ≥80% showed increased risk (adjusted HR, 1.96 [95% CI, 1.23–3.08]; P=0.004; 2.16 [95% CI, 1.33–3.52]; P=0.002, respectively). A greater extracellular volume fraction was associated with an LVEF of 70% to 80% and ≥80% (adjusted odds ratios, 1.34 [95% CI, 1.03–1.74]; P=0.027; and 1.74 [95% CI, 1.30–2.34]; P<0.001, respectively). Conclusions LVEF >70% demonstrated increased event rates compared with an LVEF of 60% to 70%. The supranormal LVEF warrants further investigation into its pathogenesis and management.